THE REAL TAMBO OF TAPARAKU (HUANUCO - PERU) - Serrudo Torobeo, Eberth (2002)
In the present work the author makes an analysis and interpretation about the function that architectonic structures ofTaparaku should have, resting above the space distribution and its analogy with other settlements of the same age, letting him define possible areas ofactivity inside the settlement. In spite of the conclusions, which are preliminaries, these must be the starts point offuture researches that include excavations in the archeological site.